C-HYFLUR: Recovery for power-off failure in flash memory storage systems using compression scheme for hybrid flush recovery - Chung, Ji Hwan; Kim, Sungsoo; Chung, Tae Sun (Lecture Notes in Electrical Engineering, 2018)
Flash memory has a variety of advantages such as the better performance compare to hard disk, shock resistance, small size, and so on. Therefore the use ratio of flash memory is being increased. But if the power-off failure is occurred, flash memory storage systems may loss mapping information. So in this paper, we propose power-off recovery scheme, called C-HYFLUR. We have applied C-HYFLUR to page mapping FTL and implemented on a platform board, and compared with the existing recovery schemes through several evaluations. Compare to existing recovery schemes, the overhead of C-HYFLUR is very low.
Keywords: Compression scheme; Failure recovery; Flash memory storage systems; Mapping information; Page mappings; Power off recovery; Recovery scheme; Shock resistance; Compression; Flash memory; FTL; Power-off failure recovery